Dinamika Permasalahan Pernikahan Hubungan Jarak Jauh (Long Distance Relationship) - David Ilham Yusuf (Fakultas Dakwah UIN KHAS Jember, 2025)
This research aims to deepen and analyze the various types of ecological application models to maintain mental health in society. Ecology has a role not only in biological health but also in mental health in humans. This research method uses a qualitative research approach. LR (Literature Review) with primary source data, namely research articles for the period 2021-2025, the data collection technique uses the application Publish or Perish by using keywords